PENERAPAN NILAI – NILAI DASAR BUDAYA KERJA DAN PRINSIP-PRINSIP ORGANISASI BUDAYA KERJA PEMERINTAH DENGAN BAIK DAN BENAR - Dezonda R Pattipawae (SASI, 2011)
Organisational culture is important when faced with efforts to improve organizational performance and employees therein. Many people do not realize that a work keberhsilan rooted in those values originated from the customs, habits, religious and other rules into confidence and then became a habit in people's behavior in carrying out the work. The values that have become a habit is called culture. Because culture is associated with higher levels of quality work, then called the culture of work culture, both inside and outside the organization. In connection with the professional values espoused, the employee should be adaptive to changes in the value of organizational culture. Attitudes toward the organization's culture becomes more meaningful in accelerating or slowing down of this adaptive ability. If employees have individual values that conflict with organizational culture, this suggests a low level of effectiveness, and vice versa. In this case there should be clear how the fact that employee attitudes towards the prevailing organizational culture. If an employee shows a good attitude towards the organization's culture, it is expected to easily form an organization of social behavior.